1998
DOI: 10.1029/97jd02644
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory studies of the influence of the rime accretion rate on charge transfer during crystal/graupel collisions

Abstract: Abstract. The process of thunderstorm electrification by charge transfers between ice crystals and riming graupel pellets (the noninductive process) has been the subject of extensive study in the laboratory in Manchester. Quantitative dependencies of the sign and magnitude of charge transfer have previously been determined as functions of ice crystal size, graupel/crystal relative velocity, temperature, and the effective liquid water content (EW) in the cloud experienced by the riming graupel pellets. We now p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
244
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(268 citation statements)
references
References 22 publications
5
244
0
Order By: Relevance
“…The polarity of charges carried by ice particles after the rebounding collision depends on the difference between the RAR and the RARC [34]. If RAR > RARC, then the graupel particles carry positive charge and the rebounding ice crystals or snow particles carry negative charge.…”
Section: Response Of Aerosol Effects On the Charge Structures To The mentioning
confidence: 99%
See 2 more Smart Citations
“…The polarity of charges carried by ice particles after the rebounding collision depends on the difference between the RAR and the RARC [34]. If RAR > RARC, then the graupel particles carry positive charge and the rebounding ice crystals or snow particles carry negative charge.…”
Section: Response Of Aerosol Effects On the Charge Structures To The mentioning
confidence: 99%
“…Under conditions with a low water vapor content, increasing aerosol concentrations did not lead to a reversal of charge carried by the ice particles, resulting in similar charge structures between clean and polluted simulations. The polarity of charges carried by ice particles after the rebounding collision depends on the difference between the RAR and the RAR C [34]. If RAR > RAR C , then the graupel particles carry positive charge and the rebounding ice crystals or snow particles carry negative charge.…”
Section: Aerosol Effects On the Intensity Of Electrical Activity And mentioning
confidence: 99%
See 1 more Smart Citation
“…In their study, in the temperature range - Rime accretion can heat the target sufficiently for it to sublimate; equation (3) relates the rime surface temperature to A mechanism proposed by Baker et al [1987] and developed by Jayaratne [1993] relies on the relative growth rates of the interacting particles; in their hypothesis the particle whose surface grows fastest by vapor diffusion charges positively. This mechanism has been used by Saunders and Peck [1998] to account for their results in which the rimer charges negatively at low EW and positively at high EW. For low EW, the heat from rime accretion ensures that the rimer grows by diffusion slower than the crystals, and so the rimer charges negatively.…”
Section: Wet Growthmentioning
confidence: 99%
“…Larger collisional losses will, of course, produce greater depths. 1997; Saunders and Peck, 1998;Jayaratne, 1996Jayaratne, , 1998], and functional equations have been fitted to the data over limited regimes. Keith and Saunders [1990] showed that the charge transfer to the target depended on crystal size and speed as power laws, with exponents varying over particular ranges of size and temperature in the positive and negative charging regimes.…”
Section: Application Of the Theory To Charging Inmentioning
confidence: 99%